Environmental stress aspects of saltgrass [Distichlis spicata (L.) Greene] - Shahba, Mohamed Ahmed, author; Qian, Yaling, advisor; Hughes, Harrison G., advisor; Wallner, Stephen, committee member; Brick, Mark A., committee member (Colorado State University. Libraries, 2002)
Saltgrass [Distichlis spicata (L.) Greene] is undergoing preliminary evaluation at Colorado State University for use as a turfgrass in adverse environments. Furthermore, it has a potential as a range species in saline-alkali basins and many of the salt marsh areas in addition to its importance for wildlife. In cooperation with a saltgrass breeding project, the objectives of this dissertation work were to: (a) determine freezing tolerance of saltgrass; (b) determine the relationship between freezing tolerance and nonstructural carbohydrate content; and (c) determine nitrogen requirements and to evaluate the nutritive value of saltgrass as affected by N levels. Stolons of saltgrass accessions were sampled at monthly intervals from October 1999 to April 2000 and from October 2000 through April 2001 and subjected to laboratory freezing tests. Parts of the sampled stolons were used to assess soluble carbohydrates, including sucrose, fructose, glucose, raffinose and stachyose using gas chromatography (GC). Results indicated significant differences among accessions in LT50 (subfreezing temperature resulting in 50% mortality) and carbohydrate content. Ranking of accessions for LT50 (°C) during January, 2000 was A29 = 48 (-20.0) > 55 (-17.0) ≥ 32 (-15.5) ≥ A65 = C66 (-14.0). In January, 2001 they were ranked with 48 = 55 (-26.0) > A65 = 32 (-23.0) > A29 (-20.0) = C66 (-18.5). Sucrose was the predominant sugar, but did not show a clear seasonal trend and had no correlation with freezing tolerance. Fructose, glucose, raffinose and stachyose exhibited clear seasonal changes, showing highest concentrations during mid-winter. Higher fructose, glucose, or raffinose concentrations were frequently observed in accessions 48, 55, and A29, which coincided with their lowest LT50. In contrast, C66 had the lowest sugar concentrations overall, which related to its sensitivity to lower temperatures. Accessions A24 and A138 were planted in the field at the Horticulture Research Center, Fort Collins, CO. to determine the nitrogen requirements for these accessions during establishment and to evaluate their nutrient content as related to nitrogen level. Results indicated positive linear relationships between cover %, productivity, tissue nitrogen and protein contents with applied nitrogen levels in both seasons. Ca, P and Fe had a positive association while Na, S and Mg had a negative association with nitrogen levels. Establishment in terms of cover and productivity, and nutritive value of the two tested saltgrass accessions increased with increasing N fertilization rate. However, nitrogen had no effect during the first month of establishment on cover when water was critical. Plots which received total of 450 kg/ha showed the best cover percentage.
Covers not scanned.
Keywords: Distichlis spicata